1998
DOI: 10.1063/1.477122
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of macromolecules in good solvents: Comparison with dielectric spectroscopy experiments

Abstract: Molecular dynamics simulations are employed to study the static and dynamic properties of macromolecules in dilute and semidilute solutions of a good solvent. The results are compared with dielectric spectroscopy experiments. Crossover concentrations, *, that demarcate the dilute and semidilute regimes are identified. The shift from self-avoiding-walk to random-walk behavior is also studied. An investigation is conducted of the normal-mode dielectric relaxation of type-A polar polymers. In dilute systems, a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 33 publications
6
36
0
Order By: Relevance
“…1 Comparing our results with dielectric data we reached the same mapping for PI as the one proposed by Kremer and Grest. We identified crossover concentrations * that demarcate the dilute and semidilute regimes.…”
Section: ͑12͒supporting
confidence: 81%
See 2 more Smart Citations
“…1 Comparing our results with dielectric data we reached the same mapping for PI as the one proposed by Kremer and Grest. We identified crossover concentrations * that demarcate the dilute and semidilute regimes.…”
Section: ͑12͒supporting
confidence: 81%
“…͑1.2͒, only the autocorrelation terms are considered, as it has been shown that cross-correlation terms are negligible for homogeneous solutions. 1,6 Using dielectric spectroscopy, Adachi and co-workers, 6-10 Imanishi and co-workers, 11,12 and Boese and Kremer 13 have investigated extensively the normal-mode relaxation of cis-polyisoprene ͑PI͒, a type-A polar polymer, in concentrated solutions and melts. There is a number of issues that were raised in these studies and it is of interest to employ molecular dynamics simulations to clarify them.…”
Section: ͑12͒mentioning
confidence: 99%
See 1 more Smart Citation
“…A clear but less remarkable broadening is also shown in the simulation curves. A recent molecular dynamics study 26) also shows the same feature. In order to understand the origin of the differences between the Monte Carlo data and the Rouse theory, we have now fitted the q (t) Monte Carlo data to the expression…”
Section: Resultssupporting
confidence: 57%
“…(12) and (13). Recent molecular dynamics simulations 26) also conclude that there is a range of chain lengths where the dielectric spectra are broadened due to chain overlapping but the normal mode relaxation times are not influenced by entanglement effects. It should be also noted that Watanabe et al 27) have explained the broad dielectric spectrum of the dielectric curves through the effect of non-sinusoidal normal modes.…”
Section: Resultsmentioning
confidence: 87%